A note on the diversity of rare and wild fruits species in Sungai Kangkawat rs, Imbak Canyon Conservation Area (ICCA), Tongod, Sabah, Malaysia - Mohd Norfaizal G; Anuar Rasyidi MN; A. Latiff; Monica Suleiman (Universiti Malaysia Sabah, 2021)
Rare and wild fruits diversity of Sungai Kangkawat Research Station, Imbak Canyon Conservation Area (ICCA), Tongod District, Sabah Malaysia was inventorised for flora composition assessment. A total of 34 species of rare and wild fruits species were identified along three trails, namely Kawang, Nepenthes and Pelajau. During this inventory trip, only a few species were fruting due to unsynchronized fruiting season. The inventorised species consist of 21 important genera namely Artocarpus, Alstonia, Aralidium, Baccaurea, Cissus, Cnestis, Durio, Diospyros, Dacryodes, Ficus, Garcinia, Gironniera, Goniothalamus, Horsfieldia, Lasianthus, Lepisanthes, Lithocarpus, Mangifera, Osmosium, Rhodomyrtus and Uvaria. A total of 61 herbarium specimens from various wild species were also collected and prepared from the trails for safe deposition at the respective herbaria